2016
DOI: 10.3389/fphar.2016.00450
|View full text |Cite
|
Sign up to set email alerts
|

Oral Administration of Sitagliptin Activates CREB and Is Neuroprotective in Murine Model of Brain Trauma

Abstract: Introduction: Traumatic brain injury is a major cause of mortality and morbidity. We have previously shown that the injectable glucagon-like peptide-1 (GLP-1) analog, liraglutide, significantly improved the outcome in mice after severe traumatic brain injury (TBI). In this study we are interested in the effects of oral treatment of a different class of GLP-1 based therapy, dipeptidyl peptidase IV (DPP-IV) inhibition on mice after TBI. DPP-IV inhibitors reduce the degradation of endogenous GLP-1 and extend circ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 37 publications
0
17
0
2
Order By: Relevance
“…Previous studies have shown that the neuroprotective effect of gliptins is glucose‐independent and is associated with activation of the GLP‐1 system 12‐16,28 . Enhanced incretin by gliptins results in attenuation of inflammatory responses, oxidative stress, mitochondrial dysfunction, tau phosphorylation, and disease‐related pathologies 12‐13,15‐16,19,27,28 . We found that blood and brain levels of active GLP‐1 are both increased after sitagliptin treatment.…”
Section: Discussionmentioning
confidence: 77%
See 3 more Smart Citations
“…Previous studies have shown that the neuroprotective effect of gliptins is glucose‐independent and is associated with activation of the GLP‐1 system 12‐16,28 . Enhanced incretin by gliptins results in attenuation of inflammatory responses, oxidative stress, mitochondrial dysfunction, tau phosphorylation, and disease‐related pathologies 12‐13,15‐16,19,27,28 . We found that blood and brain levels of active GLP‐1 are both increased after sitagliptin treatment.…”
Section: Discussionmentioning
confidence: 77%
“…Gliptins reduce neurodegeneration after acute focal cerebral ischemia 14 or chronic cerebral hypo‐perfusion 18 in nondiabetic animals. A recent study in a stereotactic cryo‐lesion model indicates that presurgical treatment with sitaglipin reduced lesioned size and activated the neuroprotective cAMP response element binding protein system in brain of female C57B16/j mice 19 . Taken together, these data suggest that gliptins have preventive neuroprotective effects in both diabetic and nondiabetic animals.…”
Section: Introductionmentioning
confidence: 78%
See 2 more Smart Citations
“…The DPP-4 inhibitors have not been extensively investigated for TBI treatment. A recent study from DellaValle et al [ 131 ] demonstrated that oral administration of sitagliptin reduces brain lesion size and brain cell death via activation of the CREB-mediated signaling pathway in the TBI mouse model; moreover, CREB-regulated expression of manganese superoxide dismutase (MnSOD) was increased in sitagliptin-treated mice. All these lines of evidence from previous studies indicate agonists of GLP-1R have potential as pharmacological-based therapies for TBI.…”
Section: The Glucagon-like Peptide-1 Receptor (Glp-1r) In Neurologmentioning
confidence: 99%